Cells and Batteries
By using adhesives with high swelling and low swelling rates in the inner and outer layers of the battery cell, respectively, to adjust the adhesive relationship, the problem of huge adhesion in the thickness direction of the battery cell is solved, and the circulation performance and production efficiency of the battery are improved.
Patent Information
- Application Number
- CN202411854276.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing battery cells have a huge adhesion gap in the thickness direction, resulting in high internal stress, affecting the cycling performance and production efficiency of the battery.
Different adhesives are used in the inner and outer layers of the battery cell respectively. The swelling rate of the first adhesive is higher than that of the second adhesive. By adjusting the adhesive force relationship (-1≤A1-A2≤4), the bonding effect between the positive electrode sheet and the separator and the wetting property of the electrolyte are balanced.
Through this method, the cycling performance of the battery can be improved, the internal resistance of DC can be reduced, and the production efficiency can be improved, which solves the problem of huge adhesion gap.
Smart Images

Figure CN119447309B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to battery cells and batteries. Background Art
[0002] In order to improve the energy density of the battery cell, the size of the battery cell is getting bigger and bigger, and the thickness of the battery cell is getting thicker and thicker. Relatively speaking, the outer electrode of the battery cell is easier to be infiltrated with the electrolyte, and it is easier to have good adhesion with the glue-coated diaphragm (when the core is hot-pressed, the glue coating on the outer diaphragm is heated first, and it is easier to bond with the glue layer on the diaphragm under pressure, while the temperature of the diaphragm glue layer close to the inner layer of the core is relatively lower, and the coating and the positive electrode are relatively poorer), while the inner electrode is more difficult to be infiltrated with the electrolyte (after injection, the electrolyte preferentially infiltrates the positive electrode near the outer layer of the core, while the diffusion of the electrolyte in the inner layer becomes difficult, and it is more difficult to infiltrate the positive electrode), and it is more difficult to have good adhesion with the glue-coated diaphragm, so the inner layer of the core has a relatively high risk of interfacial lithium precipitation due to poor wettability, and the bonding effect of the positive electrode of the core will be deviated.
[0003] At present, the formula of the positive electrode sheets of the outer and inner layers of the battery cell is the same, and the coating process is also the same, which makes it relatively difficult for the electrolyte to penetrate into the inner positive electrode sheet; and the adhesion between the inner positive electrode sheet and the coated diaphragm is also worse, but the adhesion of the outer layer is relatively large, resulting in a large disparity in adhesion across the entire thickness, and relatively high internal stress. At present, the main method to improve the wettability of the inner positive electrode sheet is to increase the standing time after the battery cell is injected, which will relatively affect the efficiency, and to increase the hot pressing time of the battery cell to improve the adhesion of the inner positive electrode sheet, which will also affect the hot pressing time. Summary of the invention
[0004] In view of this, the present invention provides a battery cell and a battery. Different adhesives are used for the positive electrode sheet active material layers corresponding to the inner layer area and the outer layer area of the battery cell, so as to balance the bonding effect of the positive electrode sheet and the diaphragm inside the entire core package, the electrolyte wettability and the production efficiency.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a battery cell, which includes a battery cell inner layer region and a battery cell outer layer region from the center to the edge of the battery cell;
[0007] The battery cell includes a positive electrode sheet, a negative electrode sheet and a separator, the positive electrode sheet includes a first positive electrode sheet and a second positive electrode sheet, the first positive electrode sheet is arranged in the inner layer area of the battery cell, and the second positive electrode sheet is arranged in the outer layer area of the battery cell;
[0008] The first positive electrode sheet includes a first active material layer, and the first active material layer includes a first active material and a first binder;
[0009] The second positive electrode sheet includes a second active material layer, and the second active material layer includes a second active material and a second binder;
[0010] The swelling rate of the first binder is greater than the swelling rate of the second binder;
[0011] The bonding force between the first positive electrode sheet and the separator is recorded as A1, and the bonding force between the second positive electrode sheet and the separator is recorded as A2. A1 and A2 satisfy the following relationship:
[0012] -1≤A1-A2≤4.
[0013] Preferably, the swelling ratio of the first binder is 41% to 52%.
[0014] Preferably, the swelling ratio of the second binder is 33% to 41%.
[0015] Preferably, the bonding strength between the first positive electrode sheet and the separator is 9 to 14 N / m.
[0016] Preferably, the bonding strength between the second positive electrode sheet and the separator is 9 to 11 N / m.
[0017] In an embodiment of the present invention, the first binder includes at least one of carboxyl-modified PVDF, hydroxyl-modified PVDF, and hyperbranched modified PVDF.
[0018] In an embodiment of the present invention, the second binder includes at least one of PVDF, trifluoroethylene-modified PVDF, hexafluoropropylene-modified PVDF, and tetrafluoroethylene-modified PVDF.
[0019] Preferably, the first active material layer includes, by weight, 93.2 to 100 parts of the first active material, 1 to 3.5 parts of the first binder, 0 to 3 parts of the first conductive agent, and 0 to 0.3 parts of the first dispersant.
[0020] Preferably, the first active material layer includes, by weight, 93.2 to 100 parts of the first active material, 1 to 3 parts of the first binder, 0 to 3 parts of the first conductive agent, and 0 to 0.2 parts of the first dispersant.
[0021] Preferably, the second active material layer includes, by mass, 93.2 to 99.5 parts of the second active material, 1 to 3.5 parts of the second binder, 0 to 3 parts of the second conductive agent, and 0 to 0.3 parts of the second dispersant.
[0022] Preferably, the second active material layer includes, by weight, 93.2 to 99.5 parts of the second active material, 1 to 3 parts of the second binder, 0 to 3 parts of the second conductive agent, and 0 to 0.2 parts of the second dispersant.
[0023] Preferably, the inner layer area of the battery cell accounts for 10% to 75% of the overall thickness of the battery cell.
[0024] In an embodiment of the present invention, the battery cell is a wound battery cell or a laminated battery cell.
[0025] In a second aspect, the present invention provides a battery comprising the above-mentioned battery cell.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] In the present invention, the first positive electrode sheet arranged in the inner layer area of the battery core includes a first binder, and the outer layer area of the battery core includes a second binder. Among them, the first binder has more polar functional groups, which is conducive to mutual diffusion with the PVDF molecular chain, improves the swelling rate and adhesion, makes the electrode sheet and the electrolyte wettability better, and the corresponding positive electrode sheet is more flexible, and it is easier to anchor and bond with the diaphragm during hot pressing, thereby reducing the DC internal resistance of the battery, which is conducive to improving the cycle performance of the battery; the swelling rate and adhesion of the second binder are relatively small, and the binder makes the electrode sheet and the electrolyte wettability relatively poor, but because the diffusion distance of the electrolyte infiltration is shorter, it can meet the wettability requirements, the corresponding electrode sheet has some flexibility deviation, it heats up faster during hot pressing, and is easier to bond with the diaphragm. Therefore, the present invention can ultimately achieve comprehensive production efficiency, balance the bonding effect of the positive electrode sheet and the diaphragm inside the entire core package, the electrolyte wettability and the purpose of production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the division of the inner and outer areas of the wound battery cell.
[0029] Figure 2 It is the division of the inner and outer areas in the laminated battery cell.
[0030] Figure 3 It is a schematic diagram of the structure of the positive electrode sheet of the present invention that has not been cut or wound.
[0031] Figure 4 It is a schematic diagram of the structure of the wound battery cell of the present invention.
[0032] The reference numerals are as follows:
[0033] 1: positive electrode;
[0034] 2: Negative electrode;
[0035] 3: Diaphragm. DETAILED DESCRIPTION
[0036] The present invention discloses a battery cell and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0037] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0038] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0041] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0042] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0043] Specifically, the present invention adopts the following technical solutions:
[0044] In a first aspect, the present invention provides a battery cell, which includes a battery cell inner layer region and a battery cell outer layer region from the center to the edge of the battery cell;
[0045] The battery cell includes a positive electrode sheet, a negative electrode sheet and a separator, the positive electrode sheet includes a first positive electrode sheet and a second positive electrode sheet, the first positive electrode sheet is arranged in the inner layer area of the battery cell, and the second positive electrode sheet is arranged in the outer layer area of the battery cell;
[0046] The first positive electrode sheet includes a first active material layer, and the first active material layer includes a first active material and a first binder;
[0047] The second positive electrode sheet includes a second active material layer, and the second active material layer includes a second active material and a second binder;
[0048] The swelling rate of the first binder is greater than the swelling rate of the second binder;
[0049] The bonding force between the first positive electrode sheet and the separator is recorded as A1, and the bonding force between the second positive electrode sheet and the separator is recorded as A2. A1 and A2 satisfy the following relationship:
[0050] -1≤A1-A2≤4.
[0051] In an embodiment of the present invention, Figure 1 and Figure 2 As shown, the inner region of the battery core refers to the region close to the vertical center axis of the battery core, and the outer region of the battery core refers to the region away from the vertical center axis of the battery core. Figure 1 As shown, the inner layer area of the battery cell refers to the area closer to the vertical center axis in the multilayer structure of the winding structure after the pole piece is wound along the vertical center axis to form a winding structure, accounting for 10% to 75% of the overall thickness of the battery cell (denoted as H), and the outer layer area of the battery cell refers to the area farther from the vertical center axis of the winding structure, accounting for 25% to 90% of the overall thickness of the battery cell. For example, the battery cell is a laminated battery cell, such as Figure 2 As shown, the inner layer area of the battery cell refers to the area closer to the vertical center axis in the multilayer structure of the stacked structure after the pole pieces are stacked along the vertical center axis to form a stacked structure, and occupies 10% to 75% of the overall thickness of the battery cell (denoted as H). The outer layer area of the battery cell refers to the area farther from the vertical center axis of the stacked structure, and occupies 25% to 90% of the overall thickness of the battery cell.
[0052] In the prior art, it is more difficult for electrolyte to penetrate into the positive electrode sheet in the inner layer of the battery cell than in the outer layer of the battery cell, and the bonding strength between the positive electrode sheet in the inner layer of the battery cell and the adhesive diaphragm is also worse, but the bonding strength between the positive electrode sheet in the outer layer of the battery cell and the adhesive diaphragm is larger, resulting in a large disparity in bonding strength across the entire thickness, and relatively high internal stress. In the present invention, the first positive electrode sheet disposed in the inner layer of the battery cell includes a first binder, and the outer layer of the battery cell includes a second binder. Among them, the first binder has more polar functional groups, which is conducive to mutual diffusion with the PVDF molecular chains in the diaphragm, improving the swelling rate and adhesion, making the electrode sheet better infiltrative with the electrolyte, and the corresponding positive electrode sheet has better flexibility, and is easier to anchor and bond with the diaphragm during hot pressing, thereby reducing the DC internal resistance of the battery, which is beneficial to improving the battery's cycle performance; the second binder has a smaller swelling rate and adhesion, and this binder makes the electrode sheet relatively less wettable with the electrolyte, but because the diffusion distance of the electrolyte infiltration is shorter, it can meet the wettability requirements, and the corresponding electrode sheet has some flexibility deviation, and it heats up faster during hot pressing, and is easier to bond with the diaphragm.
[0053] In the embodiment of the present invention, the value of A1-A2 is -1 to 4. Exemplarily, the value of A1-A2 is any value among -1, -0.6, 0, 1, 1.9, 2, 2.6, 2.7, 3, 3.3, 4 or any value within the range consisting of any two of the above values.
[0054] Preferably, the swelling rate of the first binder is 41% to 52%. Exemplarily, the swelling rate of the first binder is any value among 41%, 43%, 45%, 48%, 50%, 52%, or any value within the range consisting of any two of the above values.
[0055] Preferably, the swelling rate of the second binder is 33% to 41%. Exemplarily, the swelling rate of the second binder is any value among 33%, 35%, 37%, 39%, 41%, or any value within the range consisting of any two of the above values.
[0056] Preferably, the bonding strength between the first positive electrode sheet and the separator is 9 to 14 N / m. Exemplarily, the bonding strength between the first positive electrode sheet and the separator is any value among 9 N / m, 9.6 N / m, 10 N / m, 11 N / m, 11.5 N / m, 12 N / m, 12.7 N / m, 12.8 N / m, 13 N / m, 13.5 N / m, and 14 N / m, or any value within the range consisting of any two of the above values.
[0057] Preferably, the bonding strength between the second positive electrode sheet and the separator is 9 to 11 N / m. Exemplarily, the bonding strength between the second positive electrode sheet and the separator is any value among 9 N / m, 9.5 N / m, 9.6 N / m, 10 N / m, 10.2 N / m, 10.5 N / m, 10.8 N / m, 11 N / m, or any value within the range consisting of any two of the above values.
[0058] In an embodiment of the present invention, the first binder includes but is not limited to at least one of carboxyl-modified PVDF, hydroxyl-modified PVDF (swelling rate of 43% to 45%), and hyperbranched modified PVDF (swelling rate of 50% to 52%). Among them, carboxyl-modified PVDF includes monocarboxylic acid-modified PVDF (swelling rate of 41% to 43%) and polycarboxylic acid-modified PVDF (swelling rate of 45% to 48%). The first binder has more polar functional groups, which is conducive to forming a stronger hydrogen bond interaction with the coating molecules on the glue-coated diaphragm, thereby improving the bonding force with the glue-coated diaphragm. In addition, the electrolyte swelling rate corresponding to the first binder is higher than that of the conventional second binder, which is conducive to improving the wettability of the pole piece and the electrolyte, thereby reducing the DC internal resistance of the battery and improving the cycle performance of the battery.
[0059] In an embodiment of the present invention, the second binder includes but is not limited to at least one of PVDF (swelling rate is 33%~35%), trifluoroethylene-modified PVDF (swelling rate is 35%~37%), hexafluoropropylene-modified PVDF (swelling rate is 37%~39%), and tetrafluoroethylene-modified PVDF (swelling rate is 39%~41%).
[0060] Preferably, the first active material layer includes 93.2 to 100 parts of the first active material, 1 to 3.5 parts of the first binder, 0 to 3 parts of the first conductive agent, and 0 to 0.3 parts of the first dispersant, by weight. Exemplarily, the first active material layer includes 97.5 parts of the first active material, 1.5 parts of the first binder, 1 part of the first conductive agent, and 0.2 parts of the first dispersant, or 98.5 parts of the first active material, 1.5 parts of the first binder, 0 parts of the first conductive agent, and 0 parts of the first dispersant, or 93.2 parts of the first active material, 3.5 parts of the first binder, 3 parts of the first conductive agent, and 0.3 parts of the first dispersant, or 100 parts of the first active material, 1 part of the first binder, 0 parts of the first conductive agent, and 0 parts of the first dispersant.
[0061] Preferably, the first active material layer includes, by weight, 93.2 to 100 parts of the first active material, 1 to 3 parts of the first binder, 0 to 3 parts of the first conductive agent, and 0 to 0.2 parts of the first dispersant.
[0062] Preferably, the second active material layer includes 93.2 to 99.5 parts of the second active material, 1 to 3.5 parts of the second binder, 0 to 3 parts of the second conductive agent, and 0 to 0.3 parts of the second dispersant, by weight. Exemplarily, the second active material layer includes 96.8 parts of the second active material, 2 parts of the second binder, 1 part of the second conductive agent, and 0.2 parts of the second dispersant, or 98 parts of the second active material, 2 parts of the second binder, 0 parts of the second conductive agent, and 0 parts of the second dispersant, or 93.2 parts of the second active material, 3.5 parts of the second binder, 3 parts of the second conductive agent, and 0.3 parts of the second dispersant, or 99.5 parts of the second active material, 1 part of the second binder, 0 parts of the second conductive agent, and 0 parts of the second dispersant.
[0063] Preferably, the second active material layer includes, by weight, 93.2 to 99.5 parts of the second active material, 1 to 3 parts of the second binder, 0 to 3 parts of the second conductive agent, and 0 to 0.2 parts of the second dispersant.
[0064] In the embodiment of the present invention, depending on whether the active material is coated with carbon material, the first active material layer or the first active material layer may be added with or without a conductive agent. For example, a carbon-coated positive electrode active material does not need to add a conductive agent, while a positive electrode active material not coated with carbon needs to add a conductive agent.
[0065] In the embodiment of the present invention, for different types of active materials, the first active material layer or the first active material layer may or may not be added with a dispersant. For example, lithium iron phosphate positive electrode active materials need to add a dispersant, while ternary positive electrode active materials such as lithium nickel cobalt manganese oxide do not need to add a dispersant.
[0066] Preferably, the inner layer area of the battery cell accounts for 10% to 75% of the overall thickness of the battery cell. Exemplarily, the inner layer area of the battery cell accounts for any value of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 75% of the overall thickness of the battery cell, or any value within the range of any two of the above values.
[0067] Preferably, the thickness of the first active material layer and the second active material layer are independently 80 to 260 μm. Exemplary values are any value among 80 μm, 140 μm, 180 μm, 220 μm, and 260 μm, or any value within the range of any two of the above values. The thickness of the first active material layer and the second active material layer may be the same or different.
[0068] In an embodiment of the present invention, the first active material layer or the second active material layer is disposed on one side or both sides of the positive electrode current collector.
[0069] In an embodiment of the present invention, the positive electrode current collector is aluminum foil.
[0070] Preferably, the thickness of the positive electrode current collector is 8 to 20 μm. Exemplarily, the thickness of the positive electrode current collector is any value among 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, or any value within the range of any two of the above values.
[0071] In an embodiment of the present invention, the first active material and the second active material independently include at least one of lithium cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, lithium iron manganese phosphate, and lithium iron phosphate.
[0072] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include at least one of conductive carbon black, carbon nanotubes, graphene, and carbon nanofibers.
[0073] In an embodiment of the present invention, the first dispersant and the second dispersant independently include at least one of polyether-modified acrylate, polyether-modified phosphate, polyether-modified pyrrolidone, and acrylate-modified pyrrolidone.
[0074] In the embodiment of the present invention, the battery cell is a wound battery cell or a laminated battery cell. The specific embodiment of the present invention exemplifies a wound battery cell, but is not limited to a wound battery cell. A laminated battery cell can also implement the present invention.
[0075] In an embodiment of the present invention, the battery cell is a wound battery cell, the first positive electrode sheet and the second positive electrode sheet form a complete electrode sheet, the current collectors used by the first positive electrode sheet and the second positive electrode sheet are a continuous whole, but the active material layer components of the first positive electrode sheet and the second positive electrode sheet are different. Alternatively, the current collectors used by the first positive electrode sheet and the second positive electrode sheet are two independent entities. Alternatively, the first positive electrode sheet includes multiple first sub-positive electrode sheets, the current collectors of the multiple first sub-positive electrode sheets are multiple independent entities, and the second positive electrode sheet includes multiple second sub-positive electrode sheets, and the current collectors of the multiple second sub-positive electrode sheets are multiple independent entities.
[0076] In an embodiment of the present invention, the battery cell is a stacked battery cell, the first positive electrode sheet includes a plurality of first sub-positive electrode sheets, and the second positive electrode sheet includes a plurality of second sub-positive electrode sheets.
[0077] In a second aspect, the present invention provides a battery comprising the above-mentioned battery cell.
[0078] In the embodiment of the present invention, the battery further includes a negative electrode sheet, a separator, and an electrolyte. This application has no particular restrictions on the negative electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of this application can be achieved.
[0079] In the embodiment of the present invention, the battery is a lithium ion battery, but is not limited to lithium ion batteries. Other batteries such as sodium ion batteries, potassium ion batteries, lithium sulfur batteries, zinc ion batteries, etc. can also implement the present invention.
[0080] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0081] The reagents, instruments or materials used in the present invention can be obtained through commercial channels. The binders or modified binders used in the following examples are purchased from Arkema, Sinochem Blue Sky, East Sunshine and other companies.
[0082] The present invention will be further described below in conjunction with embodiments:
[0083] Example 1
[0084] The method for preparing the lithium ion secondary battery of this embodiment comprises the following steps:
[0085] (1) Preparation of positive electrode:
[0086] ① First positive electrode slurry: 97.5 parts of positive electrode active material (lithium iron phosphate), 1 part of conductive agent (conductive carbon black SP), 0.2 parts of dispersant (polyether modified acrylate), 1.5 parts of first binder (carboxyl modified PVDF), and appropriate amount of solvent N-methylpyrrolidone (NMP) were mixed and stirred to obtain the first positive electrode slurry with a solid content of 63%, a viscosity of 10000 mPa·s, and a fineness of 10μm;
[0087] ② Second positive electrode slurry: 96.8 parts of positive electrode active material (lithium iron phosphate), 1 part of conductive agent (conductive carbon black SP), 0.2 parts of dispersant (polyether modified acrylate), 2.0 parts of second binder (hexafluoropropylene modified PVDF), and appropriate amount of solvent NMP were mixed and stirred to obtain the second positive electrode slurry with a solid content of 63.1%, a viscosity of 9540 mPa·s, and a fineness of 10μm;
[0088] ③ The first positive electrode slurry and the second positive electrode slurry are gradually extruded and coated on the electrode foil to form the first positive electrode sheet and the second positive electrode sheet on the complete electrode sheet roll (when preparing the roll core, the first positive electrode sheet is arranged in the inner layer area of the roll core, and the second positive electrode sheet is arranged in the outer layer area of the roll core), dried, rolled, and then slit and sliced to obtain the positive electrode sheet. The structural diagram is shown in Figure 3 shown.
[0089] (2) Preparation of negative electrode sheet:
[0090] 96.5 parts of negative electrode active material (graphite), 1 part of conductive agent (conductive carbon black), 1 part of thickener (sodium carboxymethyl cellulose CMC), 1.5 parts of binder (acrylate), add deionized water to a solid content of 50% by mass, and control the viscosity to 2000 mPa·s and the fineness to 30μm to obtain a negative electrode slurry; the negative electrode slurry is extruded and coated on an electrode foil, dried, rolled, and then striped and sliced to obtain a negative electrode sheet.
[0091] (3) Diaphragm:
[0092] The diaphragm is 9+3+3+3 (3μm alumina ceramic coated on one side and 3μm PVDF coated on both sides).
[0093] (4) Battery assembly:
[0094] The positive electrode sheet, the negative electrode sheet, and the separator are wound to obtain a bare battery cell. The first positive electrode sheet is arranged in the inner layer area of the winding core, and the inner layer area of the winding core accounts for 50% of the overall thickness of the winding core. The second positive electrode sheet is arranged in the outer layer area of the winding core (such as Figure 4 As shown). Hot pressing, welding of positive and negative pole tabs, packing of bare cells in aluminum-plastic film battery shell (or aluminum battery shell / steel battery shell / nickel-plated battery shell), liquid injection, packaging, standing, formation, and capacity division, a lithium-ion secondary battery is obtained.
[0095] Example 2
[0096] The only difference between this embodiment and embodiment 1 is that the first binder of the positive electrode sheet is replaced with hydroxyl-modified PVDF.
[0097] Example 3
[0098] The only difference between this embodiment and embodiment 1 is that the first binder of the positive electrode sheet is replaced with polycarboxylic acid-modified PVDF.
[0099] Example 4
[0100] The only difference between this embodiment and embodiment 1 is that the first binder of the positive electrode sheet is replaced with hyperbranched modified PVDF.
[0101] Example 5
[0102] The only difference between this embodiment and embodiment 1 is that the amounts of the first positive electrode slurry and the second positive electrode slurry are different.
[0103] First positive electrode slurry: 98.5 parts of positive electrode active material (carbon-coated lithium iron phosphate), 0 parts of conductive agent, 0 parts of dispersant, and 1.5 parts of first binder;
[0104] Second positive electrode slurry: 98 parts of positive electrode active material (carbon-coated lithium iron phosphate), 0 parts of conductive agent, 0 parts of dispersant, and 2.0 parts of second binder.
[0105] Example 6
[0106] The only difference between this embodiment and Embodiment 1 is that the inner layer area of the core accounts for 10% of the overall thickness of the core.
[0107] Example 7
[0108] The only difference between this embodiment and Embodiment 1 is that the inner layer area of the core accounts for 75% of the overall thickness of the core.
[0109] Comparative Example 1
[0110] The only difference between this comparative example and Example 1 is the preparation of the positive electrode sheet, which is prepared as follows:
[0111] 96.8 parts of positive electrode active material (lithium iron phosphate), 1 part of conductive agent (conductive carbon black SP), 0.2 parts of dispersant (polyether modified acrylate), 2.0 parts of second binder (hexafluoropropylene modified PVDF), and appropriate amount of solvent NMP were mixed and stirred to obtain positive electrode slurry with a solid content of 63.1%, a viscosity of 9540 mPa·s, and a fineness of 10 μm;
[0112] The positive electrode slurry is extruded and coated on the electrode foil, dried, rolled, and then slit and sliced to obtain the positive electrode sheet.
[0113] Performance Testing
[0114] The positive electrode sheets and batteries of the above embodiments and comparative examples were subjected to performance tests, including:
[0115] (1) Liquid absorption time test:
[0116] Take the positive electrode sheet and use a micropipette to drop 10μL of electrolyte on the positive electrode sheet. Test the time when the electrolyte completely disappears from the electrode sheet, which is recorded as the liquid absorption time. The longer the liquid absorption time, the worse the wettability of the corresponding positive electrode sheet and the electrolyte.
[0117] (2) Diaphragm and electrode adhesion test:
[0118] The layers consisting of the diaphragm and the positive electrode sheet in the inner layer and the outer layer of the bare battery cell obtained after hot pressing in step (4) of the embodiment and the comparative example are respectively taken to obtain the first sample and the second sample, which are cut into samples with a width of 15 cm. The diaphragm at one end is gently peeled off and vertically clamped on a tensile instrument to test the adhesion between the diaphragm and the positive electrode sheet at 180°.
[0119] (3) -20℃ DC internal resistance DCR test:
[0120] At room temperature, charge the battery with 1C constant current to 3.65V, then charge it with 3.65V constant voltage to 0.05C cutoff, and then discharge it with 1C constant current to 50% SOC. Adjust the ambient temperature to -20℃, discharge it at 0.36C for 30s, and record the discharge DC internal resistance.
[0121] (4) Cycle test:
[0122] After the lithium-ion secondary battery is left to stand for 2 days at 45°C, it is first discharged at 1C to 2.0V. Then, in an environment of 25°C, a double-sided clamp with a clamp force of 3000N is used to clamp the battery. The charging process is: 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.5C, standing for 5 minutes, then 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.1C, standing for 5 minutes, then 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.05C; the discharge process is: standing for 5 minutes, 1C constant current discharge to 2.0V, and the discharge capacity at this time is recorded as the initial 1C discharge capacity; the charge and discharge cycle is performed in this way until the discharge capacity is 80% of the initial 1C constant current discharge to 2.0V capacity, and the number of cycles is recorded.
[0123] Table 1 Wettability of electrode to electrolyte and adhesion to coated diaphragm
[0124]
[0125] Note: The bonding force between the first positive electrode sheet and the separator is recorded as A1, and the bonding force between the second positive electrode sheet and the separator is recorded as A2.
[0126] From the test results of the liquid absorption time in Table 1, it can be seen that for the same formula positive electrode sheet in Comparative Example 1, the liquid absorption time of the positive electrode sheet corresponding to the inner layer of the winding core is equivalent to that of the positive electrode sheet corresponding to the outer layer of the winding core;
[0127] In Examples 1-7, the first binder corresponding to the first positive electrode sheet in the inner layer of the winding core has more polar functional groups, which is conducive to mutual diffusion with the PVDF molecular chain, thereby increasing the swelling rate and shortening the liquid absorption time, thereby making the electrode sheet better wettable with the electrolyte; the second binder corresponding to the second positive electrode sheet in the outer layer of the winding core has a smaller swelling rate and a slightly longer liquid absorption time. This binder makes the electrode sheet relatively less wettable with the electrolyte, but since the diffusion distance of the electrolyte infiltration is shorter, the wettability requirements can be met.
[0128] It can be seen from the adhesion test results in Table 1 that for the same formula positive electrode sheet in Comparative Example 1, the adhesion between the positive electrode sheet and the diaphragm corresponding to the inner layer of the winding core is significantly worse than the adhesion between the positive electrode sheet and the diaphragm corresponding to the outer layer of the winding core. This is because when the battery cell is hot-pressed, the outer diaphragm is heated first and the temperature is higher. The mutual entanglement between the molecular chains of the positive electrode binder and the PVDF in the diaphragm is stronger, and the adhesion between the corresponding diaphragm and the electrode sheet is stronger;
[0129] The first binder corresponding to the first positive electrode sheet in the inner layer of the core in Examples 1-7 has more polar functional groups, which will make the hydrogen bond interaction between the first binder and the binder molecules in the diaphragm coating stronger, and the adhesion between the first positive electrode sheet in the inner layer of the core and the coated diaphragm is greater, and increases with the increase in the number of polar functional groups in the first binder. Therefore, compared with Comparative Example 1, the adhesion between the first positive electrode sheet in the inner layer of the core and the diaphragm in Examples 1-7 has been significantly improved, and the adhesion between the inner layer of the core and the outer layer of the core is equivalent, thus solving the technical problem of large disparity in adhesion across the entire thickness;
[0130] Compared with Example 1, Example 5 does not add a conductive agent and a dispersant, but increases the amount of the first binder added. The mass proportion of the first binder increases from 14.97% of Example 1 to 15%, and the corresponding bonding force between the positive electrode sheet and the separator is larger than that of Example 1.
[0131] Table 2 Comparison of DC internal resistance and cycle performance
[0132]
[0133] It can be seen from Table 2 that compared with Comparative Example 1, the first positive electrode sheet in the inner layer of the winding core in Examples 1-7 can improve the wettability of the positive electrode sheet in the inner layer of the winding core with the electrolyte, and the corresponding DC internal resistance at -20°C is smaller.
[0134] Compared with Comparative Example 1, the first positive electrode sheet in the inner layer of the core in Examples 1-7 improves the wettability of the positive electrode sheet in the inner layer of the core with the electrolyte, which is beneficial to reducing the internal resistance of the battery cell, and the bonding effect between the positive electrode sheet and the diaphragm in the entire core package is similar, that is, the bonding strength between the first positive electrode sheet in the inner layer of the core and the diaphragm corresponding to the second positive electrode sheet in the outer layer of the core are almost the same, which is more conducive to improving the problem of electrode misalignment during the cycle and improving the cycle performance.
[0135] In Examples 1-4, as the polar functional groups corresponding to the first binder increase, the electrolyte wettability corresponding to the first positive electrode sheet becomes better (as shown in Table 1), which is beneficial to improve the diffusion of lithium ions between particles at low temperatures, thereby helping to reduce the low-temperature DC internal resistance. In addition, the bonding force between the corresponding first positive electrode sheet and the separator increases, which is beneficial to reduce the problem of electrode sheet misalignment during the cycle, thereby improving the cycle performance.
[0136] In Example 5, since the amount of conductive agent added is reduced, the adsorption of the electrolyte is reduced to a certain extent (the gaps between the conductive agent particles are conducive to the absorption of the electrolyte), so the DC internal resistance is larger than that of Example 1. However, compared with Comparative Example 1, the first binder with a higher swelling rate in Example 5 is conducive to improving the wettability of the electrolyte, and overall the DC internal resistance can still be reduced.
[0137] In Examples 6 and 7, as the thickness ratio of the first positive electrode sheet corresponding to the first binder with a higher swelling rate increases, the trend of reducing the DC internal resistance is more obvious, and the corresponding ability to improve the adhesion between the positive electrode sheet and the diaphragm is increased, thereby improving the ability to prevent the electrode sheet from being dislocated, which is beneficial to improving the cycle performance.
[0138] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A battery cell, characterized in that: From the center to the edge of the battery cell, it includes the inner layer area of the battery cell and the outer layer area of the battery cell; The battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator, the positive electrode sheet comprises a first positive electrode sheet and a second positive electrode sheet, the first positive electrode sheet is arranged in the inner layer area of the battery cell, and the second positive electrode sheet is arranged in the outer layer area of the battery cell; The first positive electrode sheet includes a first active material layer, and the first active material layer includes a first active material and a first binder; The second positive electrode sheet includes a second active material layer, and the second active material layer includes a second active material and a second binder; The swelling rate of the first binder is greater than the swelling rate of the second binder; The bonding force between the first positive electrode sheet and the separator is recorded as A1, and the bonding force between the second positive electrode sheet and the separator is recorded as A2. A1 and A2 satisfy the following relationship: -1≤A1-A2≤4; The first binder includes at least one of carboxyl-modified PVDF, hydroxyl-modified PVDF, and hyperbranched modified PVDF; The second binder includes at least one of PVDF, trifluoroethylene-modified PVDF, hexafluoropropylene-modified PVDF, and tetrafluoroethylene-modified PVDF.
2. The battery cell according to claim 1, characterized in that: The swelling rate of the first binder is 41% to 52%; The swelling rate of the second binder is 33% to 41%.
3. The battery cell according to claim 1, characterized in that: The bonding force between the first positive electrode sheet and the separator is 9 to 14 N / m; The bonding strength between the second positive electrode sheet and the separator is 9 to 11 N / m.
4. The battery cell according to claim 1, characterized in that: In parts by mass, The first active material layer includes 93.2 to 100 parts of a first active material, 1 to 3.5 parts of a first binder, 0 to 3 parts of a first conductive agent, and 0 to 0.3 parts of a first dispersant; The second active material layer includes 93.2 to 99.5 parts of a second active material, 1 to 3.5 parts of a second binder, 0 to 3 parts of a second conductive agent, and 0 to 0.3 parts of a second dispersant.
5. The battery cell according to claim 4, characterized in that: In parts by mass, The first active material layer includes 93.2 to 100 parts of a first active material, 1 to 3 parts of a first binder, 0 to 3 parts of a first conductive agent, and 0 to 0.2 parts of a first dispersant; The second active material layer includes 93.2 to 99.5 parts of a second active material, 1 to 3 parts of a second binder, 0 to 3 parts of a second conductive agent, and 0 to 0.2 parts of a second dispersant.
6. The battery cell according to claim 1, characterized in that: The inner layer area of the battery core accounts for 10% to 75% of the overall thickness of the battery core.
7. The battery cell according to any one of claims 1 to 6, characterized in that: The battery core is a wound battery core or a laminated battery core.
8. A battery, characterized in that: The battery comprises the battery cell according to any one of claims 1 to 7.
Citation Information
Patent Citations
Negative plate and battery
CN114597336A